Analysis of the Level of Knowledge of Micro, Small and Medium Enterprises (MSMEs) about Halal Product Guarantee Policies - Nur Cahyadi; Aries Kurniawan; Putra Panji Respati (IECON: International Economics and Business Conference, 2025)
Knowledge is essentially everything that is understood about a particular object, including the level of understanding in the form of science. Meanwhile, another meaning of knowledge is the result of a process after sensing a particular object. Knowledge is an important factor in behavior. This study aims to analyze the level of knowledge of Micro, Small, and Medium Enterprises (MSMEs) in Gresik Regency regarding halal product certification through the free halal certification program. Although the government has encouraged the processing of halal product certifications, there is still a gap in their utilization by MSMEs in Gresik Regency. The approach used in this study is a qualitative method with survey and in-depth interview techniques. A total of 50 MSMEs in Gresik Regency were surveyed, while 10 of them were selected for in-depth interviews. Qualitative data was used for thematic analysis to explore the understanding and experiences of MSME actors related to halal product certification. Data analysis was conducted through reduction, data presentation, and conclusion. The results of the study showed that the level of knowledge of MSME actors about halal product certification varied. The researcher used Notoatmodjo's theory of knowledge level indicators, which includes knowing, understanding, application, analysis, and synthesis. The conclusion of this study emphasizes the importance of education and training for SME actors regarding halal product certification through free halal certification programs. Therefore, policy intervention from the local government is needed to provide structured training and guidance.